COMMUNITY DEVELOPMENT THROUGH EDUCATION ON THE PROCESSING OF HOUSEHOLD WASTE INTO COMMERCIAL PRODUCTS - Widati, Alfa Akustia; Adiarto, Tokok; Zakki Fahmi, Mochamad; Budi Prasetyo, Antonius; Darmokoesoemo, Handoko; Supriyanto, Ganden; Sumarsih, Sri; Purwaningsih, Aning; Khasanah, Miratul; Hartati, Hartati; Baktir, Afaf; Hadi, Sofijan; Purkan, Purkan; Raharjo, Yanuardi; Khairunnisa, Fatiha; A'yuni, Qurrota; Tri Puspaningsih, Ni Nyoman; Hwei Voon, Lee (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
Community empowerment and household waste processing are two issues that need to be resolved by the government. An independent and educated society is an important pillar to support the development of country. Meanwhile, waste that continues to accumulate without processing has a negative impact on health and the environment. Public education about household waste processing can be a solution to the two problems above. Education was carried out at Junior High School YBPK Surabaya and residents of Dukuh Kupang Surabaya, and other participants who joined in a hibrid meeting with a total of 116 participants. Activities at YBPK Surabaya took place on 25 March and 5 August 2023 and activities at Dukuh Kupang Surabaya took place on 27 May and 26 August 2023. The types of waste processed are organic waste and used cooking oil, which are then converted into eco-enzymes and used cooking oil Activities are divided into 2 stages. there are community education activities and program sustainability monitoring activities. The community education activities includes presentation and workshop were hold in March 2023 at YBPK Surabaya Middle School and May 2023 at Dukuh Kupang Surabaya. The evaluation of sustainability program including individual practice and monitoring of activities was carried out in August 2023 at Dukuh Kupang Surabaya. Methods for implementing activities include presentation, practice accompanied by a mentor, individual practice, and monitoring program sustainability. Based on the analysis of participants' ability, the participant scores before and after the activity was increase. It means that this training succeeded in increasing participants' knowledge and skills in processing waste, especially organic waste and used cooking oil waste. A total of 72 out of 116 participants (62%) had processed household waste either individually or in groups. Activity evaluation data shows that these activities are necessary and on target to create an independent and creative society.